THE EFFECT OF PROFESSIONALISM ON EMPLOYEE WORK PRODUCTIVITY AT SAKURA JAYA COMPANY - Rinintha Parameswari; Fidelis Wato Tholok; Pujiarti Pujiarti (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
The more professional human resources are in control, the vision and mission and goals of the company will be achieved effectively, efficiently, and productively (Budiharjo, 2015: 5). Therefore, human resource management is needed that is not only able to recruit it, but able to retain competent employees and improve the performance of its employees so the company can continue to develop better and be able to compete with its competitors (Budiharjo, 2015: 8). The results showed that: 1) There was an influence of professionalism on employee work productivity, as evidenced by the tcount for the Professionalism (X) variable of 20,830, while the t-table value for N = 85 was 1,988. So 20,830> 1,988, then H0 is rejected and Ha is accepted, it can be stated that Professionalism (X) has a significant effect on Employee Productivity (Y). Probability value (significance) = 0,000. So the probability is 0,000 below 0.05. Thus, H0 is rejected and Ha is accepted, it can be concluded that there is a positive and significant effect between the professional variable (X) on the Employee Productivity variable (Y), because the probability value is smaller than 0.05. 2) There is an influence of Professionalism on Employee Work Productivity, as evidenced by the R Square value of 0.839. This shows that 83.9% Professionalism (X) affects Employee Productivity (Y), while the remaining 16.1% is influenced by other factors not examined in this study.